IL‐2 therapy preferentially expands adoptively transferred donor‐specific Tregs improving skin allograft survival - Ratnasothy, Kulachelvy; Jacob, Jacintha; Tung, Sim; Boardman, Dominic; Lechler, Robert Ian; Sanchez-Fueyo, Alberto; Martinez‐Llordella, Marc; Lombardi, Giovanna (American journal of transplantation, 2019)
Regulatory T cells (Tregs) have unique immunosuppressive properties and are essential to ensure effective immunoregulation. In animal models, Tregs have been shown to prevent autoimmune disorders and establish transplantation tolerance. Therefore, the prospect of harnessing Tregs, either by increasing their frequency or by conferring allospecificity, has prompted a growing interest in the development of immunotherapies. Here, employing a well‐established skin transplant model with a single major histocompatibility complex mismatch, we compared the therapeutic efficacy of adoptively transfer Treg with or without donor specificity and the administration of IL‐2 to promote in vivo expansion of Treg. We showed that IL‐2 treatment preferentially enhances the proliferation of the allospecific Tregs adoptively transferred in an antigen‐dependent manner. In addition, donor‐specific Tregs significantly increased the expression of regulatory‐related marker, such as CTLA4 and inducible costimulator (ICOS), in the skin allograft and draining lymph nodes compared to endogenous and polyclonal transferred Tregs. Importantly, by combining IL‐2 with donor‐specific Tregs, but not with polyclonal Tregs, a synergistic effect in prolonging skin allograft survival was observed. Altogether, our data suggest that this combination therapy could provide the appropriate conditions to enhance the immunoregulation of alloimmune responses in clinical transplantation. Combining adoptive transfer of donor‐specific Tregs with low dose IL‐2 has a synergistic effect in prolonging MHC‐class I–mismatched skin transplant survival due to antigen‐driven Treg expansion.